2010
DOI: 10.1021/jm901797p
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Tertiary Sulfonamides as Potent Liver X Receptor Antagonists

Abstract: Tertiary sulfonamides were identified in a HTS as dual liver X receptor (LXR, NR1H2, and NR1H3) ligands, and the binding affinity of the series was increased through iterative analogue synthesis. A ligand-bound cocrystal structure was determined which elucidated key interactions for high binding affinity. Further characterization of the tertiary sulfonamide series led to the identification of high affinity LXR antagonists. GSK2033 (17) is the first potent cell-active LXR antagonist described to date. 17 may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 17 publications
2
62
0
Order By: Relevance
“…1A) as an LXR antagonist that displayed high binding affinity for LXR while antagonizing LXR target gene expression in cell culture [21]. We confirmed this activity in cell based cotransfection assays where we assessed the ability of GSK2033 to suppress basal transcription LXRα and LXRβ as detected by luciferase reporters driven by either DR4 LXREs (Fig.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…1A) as an LXR antagonist that displayed high binding affinity for LXR while antagonizing LXR target gene expression in cell culture [21]. We confirmed this activity in cell based cotransfection assays where we assessed the ability of GSK2033 to suppress basal transcription LXRα and LXRβ as detected by luciferase reporters driven by either DR4 LXREs (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Here, we assessed the effects of GSK2033 in the identical mouse model of NAFLD. GSK2033 is described as a LXR antagonist [21] although we observed clear inverse agonist activity as well. GSK2033 display systemic exposure and we believed it might be a good comparison to SR9238, which displays liver specificity.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…30 Detailed SAR studies indicated that the position of the morpholinosulfonyl moiety of the F2 phenyl ring is important to modifications (Tables 1 and 2). Further analysis of the essential structural requirements for effective FXR antagonists showed that the meta-position-substituted morpholinosulfonyl moiety on the aniline amide moiety would influence the antagonistic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the LXR-deficient macrophages had higher basal levels of ABCA1, as previously reported (36), incubation with apoptotic cells significantly increased ABCA1 transcript levels in the Lxra/b -/-macrophages ( Figure 3B). In contrast, the Lxra/b -/-macrophages were completely deficient in increasing the Abca1 message in response to the LXR agonist TO-901317 (denoted 1317) ( Figure 3C) (37).…”
Section: Apoptotic Cells Induce a Transcriptional Upregulation Of Abca1mentioning
confidence: 98%